Efficiently cleaved HIV-1 envelopes: can they be important for vaccine immunogen development?. (October 2020) - Das, Supratik; Kumar, Rajesh; Ahmed, Shubbir; Parray, Hilal Ahmad; Samal, Sweety
The enormous diversity of HIV-1 is a significant impediment in selecting envelopes (Envs) that can be suitable for designing vaccine immunogens. While tremendous progress has been made in developing soluble, trimeric, native-like Env proteins, those that have elicited neutralizing antibodies (Abs) in animal models are relatively few. A strategy of selecting naturally occurring Envs suitable for immunogen design by studying the correlation between efficient cleavage on the cell surface and their selective binding to broadly neutralizing Abs (bNAbs) and not to non-neutralizing Abs (non-NAbs), properties essential in immunogens, may be useful. Here we discuss some of the challenges of developing an efficacious HIV-1 vaccine and the work done in generating soluble immunogens. We also discuss the study of naturally occurring, membrane-bound, efficiently cleaved (naturally more sensitive to furin) Envs and how they may positively add to the repertoire of HIV-1 Envs that can be used for vaccine immunogen design. However, even with such Envs, the challenges of developing well-folded, native-like trimers as soluble proteins or using other immunogen strategies such as virus-like particles with desirable antigenic properties remain, and are formidable. In spite of the progress that has been made in the HIV-1 vaccine field, an immunogen that elicits neutralizing Abs with significant breadth and potency in vaccines has still not been developed. Efficiently cleaved Envs may increase the number of available Envs suitable for immunogen design and should be studied further.